Assessment of irrigation water interval on maize in dryland in central sulawesi. Issue 1 (May 2021) - Irmadamayanti, A; Muchtar,; Wahyuni, A N; Padang, I S; Saidah,; Syafruddin,
Abstract: Dryland agriculture has many problems, one of which is the limited level of water availability. The water supply interval is able to use water efficiently with the maximum possible yield potential. This study aims to determine the time of giving water that can give optimum results in maize cultivation in dry climates. The research was conducted at the Sidondo III Agricultural Technology Research and Assessment Installation, Sigi Biromaru District, Sigi Regency, Central Sulawesi. The activity was carried out from March to July 2019. The method used was Randomized Block Design using Bima 15 Variety with four water treatment intervals (Control, 8 days, 14 days and 18 days) and each was repeated 3 (three) times. Interval treatment of giving water every 8 days gave better growth and yield compared to other water treatment intervals, namely each 114.67 cm plant height, 10.40 strands number of leaves, 1.51 cm stem diameter, 16.70 cm cob length, 4.36 cm cob diameter, 38 seeds each row, 171.33 grams of 5 cob weight sample, 26. 86 grams weight of jenggel and 6.63 tons / ha yield.